Factors Associates with Intention to Use Cannabis Oil in Patients with Non-communicable Diseases in Bangkok - Tienthong, Thanate; Suwannaroop, Nantawan; Boonyamalik, Plernpit; Kaewboonchoo, Orawan (Disease Control Journal, 2022)
This descriptive cross-sectional study aimed to explore the factors related to intention to use cannabis oil in patients with non-communicable diseases (NCDs) in Bangkok. A study sample was 402 NCD patients (heart disease, diabetes, and hypertension), both male and female, aged over 20 years old, and residing in the communities in Bangkok. Data were collected using structured interview questionnaires. Data were analyzed using descriptive and inferential statistics. Univariate analysis and multivariate analysis were performed to examine the factors associated with intention to use cannabis oil using Chi-square statistics and Multiple Logistic Regression, respectively. The results showed that 68.4% of the study sample were female, mean age 62.1 years old, and 57.0% received primary education (). Additionally, it was found that 24.6 % intended to use cannabis oil. About 62.7% was at low levels of knowledge related to cannabis oil (and 73.4% had insufficient levels of health literacy on cannabis oil use (The multivariate analysis revealed the factors significantly associated with the intention to use cannabis oil were good attitude of family members toward cannabis oil use (ORadj = 2.5, 95% CI = 1.3-4.4, p = 0.003), support from friends or acquaintances (ORadj = 2.7, 95%CI = 1.3-5.3, p = 0.004), and having health literacy of cannabis oil (ORadj = 4.5, 95% CI = 2.2-9.1, p <0.001). Therefore, the health literacy enhancement program related to cannabis oil use should be promoted among patients with NCDs and